Analisis Pengaruh Kecukupan Modal, Kredit Bermasalah, Likuiditas, dan Marjin Bunga Bersih terhadap Risiko Bisnis (Studi pada Bank Umum Swasta Nasional Devisa) - Prasetyo, Muhammad Ichsan (Jurnal Aplikasi Manajemen, 2013)
Banks is an institution which its main activity is fund raising from society then revolves the fund for thepurpose of generating revenue. Therefore it is important for bank to maintain public trust because the business activity hardly relies on the public trust. This research aims to prove the effect of Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), and Net Interest Margin (NIM) toward Standard Deviation of Return on Asset (SDROA). The object of this research is the private generalforeign-exchange banks which are listed in Indonesia Stock Exchange during 2007 - 2011. The analysis technique used is census as all of the population's members are involved as research sample. The samples are 20 private general foreign-exchange banks in Indonesia. The data are retrieved from the annual financial report from each bank's official website since 2007 to 2011. The analysis technique is multipleregression analysis. In addition, the data are secondary data. Thus, to determine the accuracy of model, it is important to test some classical assumptions underlined the regression model. During research period, it is found that the research data are normally distributed; it indicates that the available data have fulfilled the assumption to operate multiple linear regression method. The result of the hypothesis test reveals that CAR,NPL, LDR, NIM, and SIZE simultaneously and significantly affect SDROA. Among the four independent variables, only CAR, NPL, and NIM variables that have partial significant effect toward SDROA for go public general foreign-exchange banks.; thus, only LDR variable which does not bring significant effect toward SDROA.